Final Message: Communication From an Interdisciplinary Point of View – Or Communication in the Service of Individual and Social Well-Being - Váradi-Csema, Erika (Interdisciplinary and Child-Friendly Communication, 2025)
Professionals working with children face numerous challenges in their daily work, which significantly affect their well-being, mental state, and psychological well-being. However, the impactof these factors is even more significant, as they directly and indirectly influence the enforcement of children’s rights and the effectiveness of cooperation with children. These professionals often represent adult society to children. In most cases, this is when the child is vulnerable, emotionally wounded, or in need of support for some other reason. The nature of their cooperation with professionals and the experiences they gain in this way are not only important in terms of the successful handling of the specific case. A single positive experience can make a particular professional a role model for children. Their behaviour and reactions can thus become exemplary, serving as a model in the socialization process of young people. Whether we examine it on an individual or societal level, the fact remains that communication is the means to finding emotional balance or social peace. Impaired communication skills, a poorly chosen communication style, or the inability to decode and interpret the other party’s communication messages can lead to feelings of failure, frustration, and even burnout in the long run.This chapter provides a brief overview of the two main types of well-being: subjective and social well-being. The latter has a significant impact on the sensitivity of the environment surrounding younger age groups, for example in relation to the enforcement of children’s rights and the detection of violations.Keywords: definition of well-being, subjective well-being, social well-being